2008
DOI: 10.1161/hypertensionaha.107.109637
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Inhibition of ε-Protein Kinase C Attenuates Cardiac Fibrosis and Dysfunction in Hypertension-Induced Heart Failure

Abstract: Abstract-Studies on genetically manipulated mice suggest a role for -protein kinase C (PKC) in cardiac hypertrophy and in heart failure. The potential clinical relevance of these findings was tested here using a pharmacological inhibitor of PKC activity during the progression to heart failure in hypertensive Dahl rats. Dahl rats, fed an 8% high-salt diet from the age of 6 weeks, exhibited compensatory cardiac hypertrophy by 11 weeks, followed by heart failure at Ϸ17 weeks and death by the age of Ϸ20 weeks (123… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 15 publications
6
56
0
1
Order By: Relevance
“…Although olmesartan did not attenuate salt-induced hypertension ( Figure 7A), it did suppress LV hypertrophy, maintain LV systolic function, and improve survival over the duration of the study, as reported previously (data not shown). 26 Notably, olmesartan blocked the salt-induced increase in adrenal aldosterone biosynthesis ( Figure 7B …”
Section: Effects Of a High-salt Diet On The Adrenal Rasmentioning
confidence: 94%
“…Although olmesartan did not attenuate salt-induced hypertension ( Figure 7A), it did suppress LV hypertrophy, maintain LV systolic function, and improve survival over the duration of the study, as reported previously (data not shown). 26 Notably, olmesartan blocked the salt-induced increase in adrenal aldosterone biosynthesis ( Figure 7B …”
Section: Effects Of a High-salt Diet On The Adrenal Rasmentioning
confidence: 94%
“…Its sub-depressor dose is relatively variable to be determined, because earlier studies using a Dahl saltsensitive rat model have reported that 0.6 or 3 mg kg À1 day À1 of olmesartan did not lower blood pressure but that 2.5 mg kg À1 day À1 of the drug did. [15][16][17] Therefore, we have carefully carried out our preliminary study in our system and determined that 0.6 and 1 mg kg À1 day À1 of olmesartan were sub-depressor doses. Systolic blood pressure and heart rate were measured every 2 weeks with a tail-cuff system (MK-2000, Muromachi, Tokyo, Japan).…”
Section: Animal Preparationmentioning
confidence: 99%
“…Previous studies reported that Cav3 contributes to a variety of cardiac pathophysiological processes such as arrhythmogenesis, myocardial hypertrophy, and myocardial ischemia/reperfusion injury [17-19]. Cav3 was shown to be associated with protein kinase C (PKC) signaling, known to induce fibrogenesis [20-22]. PKC belongs to a family of Ser/Thr protein kinases, commonly expressed in eukaryotic cells, and several subtypes have been identified, including PKCα, PKCβ, PKCδ, and PKCε [23].…”
Section: Introductionmentioning
confidence: 99%